La motivación en equipos de ventas .Plan de motivación (2019)
This article is based on a research project carried out on big and medium companies in Colombia. The size of the sample was designed following the statistics methodology. Four hundred salespeople in big and medium Colombian companies were interviewed in order to establish the relevant aspects for the design of a motivational plan. Based on the results obtained, a design of a motivational plan is proposed by the authors, along with its objectives, elements to be taken into account, different types of motivation, and the appropriate methodology to implement such a plan.